Profil Keterampilan Memecahkan Konflik Interpersonal Siswa Berbakat Istimewa di SMA Kota Malang - Nawantara, Rosalia Dewi (Universitas Nusantara PGRI Kediri, 2021)
Gifted and talented students have very distinctive characteristics, namely having high intelligence, task commitment, and creativity. Some of these points then raise questions about how their social skills are, especially regarding interpersonal conflict solving skills. Often the advantages in the intellectual field make the assumption that the social skills of gifted and talented students are lacking. This study aims to determine the profile of interpersonal conflict solving skills of gifted and talented students at SMAN Kota Malang. The research approach used a quantitative research approach with survey research techniques and total sampling techniques. The sample used was 162 students. The research instrument used a scale of interpersonal conflict solving skills that had been tested for validity and reliability. The results showed that the most gifted and talented students' interpersonal conflict solving skills at SMAN in Malang were in the high category, namely 76%. The very high category was 22%, the moderate category was 2%, and the low and very low category was 0%. The results of this study can be used by counseling teachers in planning counseling services for gifted and talented students. Keyword: interpersonal conflict resolution skills, gifted and talented students